2015
DOI: 10.1371/journal.pone.0138070
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reading Scheme for Assessing the Extent of Radiographic Abnormalities and Its Association with Disease Severity in Sputum Smear-Positive Tuberculosis: An Observational Study in Hyderabad/India

Abstract: BackgroundExisting reading schemes for chest X-ray (CXR) used to grade the extent of disease severity at diagnosis in patients with pulmonary tuberculosis (PTB) are often based on numerical scores that summate specific radiographic features. However, since PTB is known to exhibit a wide heterogeneity in pathology, certain features might be differentially associated with clinical parameters of disease severity.ObjectiveWe aimed to grade disease severity in PTB patients at diagnosis and after completion of DOTS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…S100A8/A9 protein dimer is present in the inflammatory lung granulomas in active human PTB and in the TB mouse model these proteins mediate neutrophilic accumulation by inducing production of proinflammatory chemokines and cytokines 44 . Accordingly, our results not only suggest that neutrophils are the source of S100A12 but also that this protein is a predictor of alveolar infiltration, and we have recently shown that alveolar infiltration is associated with severity and infectivity in PTB 32 . Importantly, we measured CRP, a classical acute phase protein and indicator of immune system activity, although we found that CRP is a good predictor of disease occurrence, the serum concentration of this protein was not associated with any radiographic abnormality.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…S100A8/A9 protein dimer is present in the inflammatory lung granulomas in active human PTB and in the TB mouse model these proteins mediate neutrophilic accumulation by inducing production of proinflammatory chemokines and cytokines 44 . Accordingly, our results not only suggest that neutrophils are the source of S100A12 but also that this protein is a predictor of alveolar infiltration, and we have recently shown that alveolar infiltration is associated with severity and infectivity in PTB 32 . Importantly, we measured CRP, a classical acute phase protein and indicator of immune system activity, although we found that CRP is a good predictor of disease occurrence, the serum concentration of this protein was not associated with any radiographic abnormality.…”
Section: Discussionsupporting
confidence: 62%
“…We recently developed an assessment scheme for grading disease severity in PTB by specifically considering the five CXR manifestations: lung involvement, alveolar infiltration, cavitation, lymphadenopathy and pleural effusion, these CXR features were differently associated with Body Mass Index (BMI) and sputum smear positivity, and changed to a different extent after 6 months of treatment 32 . We used this same assessment scheme to evaluate the association of these specific CXR features with CRP, S100A12, sRAGE and WBC using regression analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the reader agreement in this study to conclude active TB with the CRRS method is good [16]. The kappa value of the CRRS method is also better when compared with the study using another method against the four features commonly seen in tuberculosis [17].…”
Section: Discussionmentioning
confidence: 75%
“…Most radiological findings were consolidation and cavity lesion accordingly. 10,12,13 Out of 53 sputum smear negative patients, Sputum culture was positive in 14 (26%) patients whereas bronchial washings smear was positive for AFB in 30 (57%) patients and bronchial washing culture was positive for AFB in 40 (75%) patients. 14 Flexible bronchoscope has become very useful tool in patient care and medical research.…”
Section: -11mentioning
confidence: 98%